2008
DOI: 10.1007/s11249-008-9340-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Adhesion Characteristics of Spherical Sliders Colliding with Stationary Magnetic Disks with a Thin Lubricant Layer

Abstract: The dynamic indentation characteristics of 1-and 2-mm-radius hemispherical glass sliders when colliding with stationary magnetic disks under various lubricant conditions were investigated to clarify the dynamic interfacial forces between flying head sliders and magnetic disks. The collision times were *15 and *30 ls, respectively, and independent of the impact velocity. For a 1-mm-radius slider (Ra roughness = 1.71 nm), a clear adhesion force nearly equal to the static pull-off force was observed at the instan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…These parameter values are the same as those of the 2-mm-radius glass slider and magnetic disk used for the dynamic adhesion force measurements [19,20]. Accurate values of the Hamaker constant and the atomic equilibrium distance are not known.…”
Section: Calculated Results For Contact Characteristics Ignoring Aspementioning
confidence: 99%
See 1 more Smart Citation
“…These parameter values are the same as those of the 2-mm-radius glass slider and magnetic disk used for the dynamic adhesion force measurements [19,20]. Accurate values of the Hamaker constant and the atomic equilibrium distance are not known.…”
Section: Calculated Results For Contact Characteristics Ignoring Aspementioning
confidence: 99%
“…Ono and Nakagawa [19,20] measured the dynamic adhesion force that was applied on the slider when 1-and 2-mm-radius glass sliders collided with a magnetic disk with a molecularly thin lubricant layer. They concluded that the adhesion force observed at the instant of separation after a short contact period of 15-30 µs was caused by the meniscus force rather than by vdW force.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the experimental results of Li et al [12], we established a theory of interfacial force caused by meniscus formation in the toe-dipping regime and performed dynamic analysis on a flying head slider using a simple two-degree-offreedom (2-DOF) model [3,6,[16][17][18]. We also experimentally investigated the dynamic adhesion force that occurs when a spherical slider collides with a magnetic disk [19,20]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The roughness of the disk was 0.52 nm, force calculated from 4pRg (R: mean asperity radius, g: lubricant surface tension ¼ 22 mN/m). The adhesion force dropped to zero when the slider travelled more than 5 nm from the initial disk surface height (details are given elsewhere [19,20]). These findings indicate that a meniscus in the flooded regime can form in a short period (15 ms) even when the surface of the glass slider is rough and that the dynamic adhesion force originates from meniscus force rather than van der Waals force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation